RACISM AGAINST INDIGENOUS PEOPLE AND AFRO-DESCENDANTS IN SWEDEN, BRAZIL, AND MEXICO - Gomes, Cristina (Seven Editora, 2024)
This article explores how racism and stigmatizing discourses and practices are articulated and normalized in colonizer and colonized countries. The research compares the cases of Sweden, Brazil, and Mexico from a combination of frameworks -- the Critical Race Theory (Walton, 2019; Ansley, 1997), the neo-Marxist concept of institutional racism and racialization (Cole, 2016 and 2020), and a decolonial framework and methodology (Fanon, 1968; Tynan and Bishop, 2022). Racism has been structural and systemic in Latin American societies since colonization when religious and royal authorities legitimated Indigenous and African slavery in the colonies. After independence, modern free republics converted religious legitimation of racism in pseudoscientific Eugenics and the invention of human races and racism continue oppressing Indigenous and African descendants. Currently structural racism continues to be the normal behavior in Western societies, not an exception.The objective of this research is to identify and compare racism reveled in behaviors and the speeches behind them in two colonized societies – Brazil and Mexico – and Sweden, a colonizing society. The question orienting the comparative research is how and in which ways racism and stigmatizing discourses and practices are articulated and normalized in colonizer and colonized countries. Understanding the main persistent trends in these societies on eugenic somatic characteristics such as hair type, body part sizes (e.g. head), as well as other collective social and religious symbols, behaviors, attitudes and cultural customs, used as discriminatory markers.The qualitative methodology includes 69 interviews and six focus groups in the three countries. Results were analyzed form a critical reflexivity about how colonialism and eugenics impact the lived experiences and realities of both groups in colonized and colonizer countries, through historic and current practices. racism has the same routes of functioning, structuring unequal relationships, distortions in the perception of the other, marginalization and suffering.DOI: https://doi.org/10.56238/sevened2024.037-072